2006
DOI: 10.1289/ehp.8674
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Air Pollution on Hospitalizations for Cardiovascular Diseasein Elderly People in Australian and New Zealand Cities

Abstract: ObjectiveThe goal of this study was to estimate the associations between outdoor air pollution and cardiovascular hospital admissions for the elderlyDesignAssociations were assessed using the case–crossover method for seven cities: Auckland and Christchurch, New Zealand; and Brisbane, Canberra, Melbourne, Perth, and Sydney Australia. Results were combined across cities using a random-effects meta-analysis and stratified for two adult age groups: 15–64 years and ≥ 65 years of age (elderly). Pollutants considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
181
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(201 citation statements)
references
References 18 publications
13
181
1
6
Order By: Relevance
“…After dividing the PM 2.5 concentration into four equal quartiles using the Q1, Q2, and Q3 divisions, compared with the reference group (the group with the lowest PM 2.5 concentration), the clinical visit incidence of patients with respiratory diseases in the other three groups increased. Previous studies (Barnett et al, 2006;Guo et al, 2010;Ma et al, 2011;Hansen et al, 2012) indicated that an increased PM 2.5 concentration causes an increased risk of respiratory diseases, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…After dividing the PM 2.5 concentration into four equal quartiles using the Q1, Q2, and Q3 divisions, compared with the reference group (the group with the lowest PM 2.5 concentration), the clinical visit incidence of patients with respiratory diseases in the other three groups increased. Previous studies (Barnett et al, 2006;Guo et al, 2010;Ma et al, 2011;Hansen et al, 2012) indicated that an increased PM 2.5 concentration causes an increased risk of respiratory diseases, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been found in Japan [35], Australia, and New Zealand [36]. In 2008, Samoli et al [37] re-analyzed the data of the APHEA 2, NMMAPS, and several Canadian studies in order to assess the coherence of findings using the same methods for all three sets of data.…”
Section: Short-term Effectsmentioning
confidence: 60%
“…While it is clear that local populations are affected by wildfire events, a growing concern is the potential health impact on geographically distant populations, specifically in susceptible groups such as the elderly. Epidemiologic research has identified the elderly, who are more likely to have pre-existing lung and heart diseases, as a population vulnerable to the effects of short-term exposures to air pollution including fine particles [24,[40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%